Transnasal humidified rapid insufflation ventilatory exchange combined with intravenous anesthesia and nerve block without endotracheal intubation for atrial septal defect repair: a case report - Shi, Haifeng; Zhou, Zhengqing; Xu, Hua (Frontiers in Anesthesiology, 2023)
This brief case report describes a new anesthesia method without endotracheal intubation in open heart surgery. The patient is a 41 years old female. Because the location of atrial septal defect is not suitable for interventional minimally invasive surgery, she can only undergo open heart surgery under cardiopulmonary bypass. Due to news reports about anesthesia without tracheal intubation, the patient refused to undergo tracheal intubation anesthesia, we innovatively adopted an anesthesia method of transnasal humidified rapid insufflation ventilatory exchange (TRIVE) combined with intravenous anesthesia and nerve block without endotracheal intubation, and achieved success. The whole operation process was very smooth, the patient was quiet and motionless, and her respiratory and circulatory stability, After the operation, the patient opened her eyes without any complaints and was safely sent to the CICU.